ANALISIS PENERAPAN BAURAN PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA MOO SUSU SAMARINDA - Wigati Pratiwi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The marketing mix is very important to be applied by business people to achieve the goal of increasing product sales and controlling the market. This study aims to determine and analyze the application of the marketing mix based on 9 elements of the marketing mix by Moo Susu Samarinda in increasing sales. The type of research used is qualitative research with a descriptive approach. In collecting data, researchers used observation, interview and documentation methods. Data analysis is done by reducing data, presenting data, and drawing conclusions. The conclusion in this study is that the marketing mix that has been implemented by Moo Susu Samarinda is not in accordance with the 9 elements of the marketing mix. The marketing mix applied by Moo Susu is Product (product) by selling contemporary beverage products with the main raw material of milk with various flavors and using quality raw materials, Price (price) by applying the method of applying prices based on cost plus, Place (place) by choosing a strategic location that is easily seen and accessed by consumers in setting up their business, Promotion (promotion) carried out is direct marketing (direct markeiing) in the form of online marketing through Instagram and partnering with Grab and Gojek, People by conducting training for 3 days to employees who have been recruited and declared accepted to work at Moo Susu and providing bonuses to motivate employees, Payment by implementing a cash and non-cash payment system for convenience and Packaging by using plastic glass packaging with a printed design of the Moo Susu logo along with the tagline and the packaging design is made directly by the business owner.